2011, No. 10, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Auditing theory and practiceLionius Gaižauskas, Understanding the total cost of ownership, 7Dalia Daujotaitė, Performance audit model based on the evaluation of financial management processes, 15Andrejus Lebedevas, Application of management assertion in audit of profit (loss) statement, 25Jonas Mackevičius, Jokūbas Leipus, Significance of audit in banks of Islamic countries, 38Accounting theory and practiceErika Ragauskienė, States’ assets: accounting and status analysis, 53Agnė Marfinaitė, Kristina Rudžionienė, Measurement and disclosure of an enterprise’s intellectual capital, 66Jonas Mackevičius, Romualdas Valkauskas, The role of Jonas Ilgūnas in the creation of accounting system in Lithuania, 74Economical problemsMartynas Vanagas, Asta Strolaitė, Accounting regulation of European Union structural funds projects‘ under the program for 2007 - 2013, 85Vytautas Kindurys, Theoretical and methodological aspects of insurance customers‘ loyalty, 99ReviewsJonas Mackevičius, Theoretical and practical aspects of investment management, 112
Keywords: none